MHSP in reversed-bias operation mode for ion blocking in gas-avalanche multipliers - Veloso, J. F. C. A. (2005)
We present recent results on the operation of gas-avalanche detectors comprising a cascade of gas electron multipliers (GEMs) and Mico-Hole & Strip Plate (MHSP) multiplier operated in reversed-bias (R-MHSP) mode. The operation mechanism of the R-MHSP is explained and its potential contribution to ion-backflow (IBF) reduction is demonstrated. IBF values of 4Ã—10-3 were obtained in cascaded R-MHSP and GEM multipliers at gains of about 104, though at the expense of reduced effective gain in the first R-MHSP multiplier in the cascade.